Power quality and stability improvement of more-electronics power systems - Fang, Jingyang (2018)
Primary drivers behind grid transformations comprise a marriage of the ever-increasing energy demand and a desire for reduction of carbon footprint. As the trend of grid transformations continues, a significantly high penetration level of renewable energy sources (RESs) is to be expected. Since renewables, in parallel with other emerging technologies such as energy storage and electric vehicles (EVs), are normally coupled to power grids through power electronic converters, power systems gradually evolve into more-electronics power systems. Despite its clear efficiency and control benefits, power electronics brings in issues to power systems. For one hand, it is difficult to ensure high-quality power supplies due to the power quality issues introduced by power electronics. For the other hand, power electronics may introduce instability issues. The instability issues should be blamed not only for the improper control of a single power converter but also for the undesirable operation of the entire power system. As power quality and stability are at the core of power system operations, this thesis aims to investigate and overcome several associated issues in the hope of smoothing the transformation towards future smart grids. First, the fundamentals of more-electronics power systems including system configurations, operating principles, and modelling and control of power converters are described. For the purpose of analysis, a single-area power system consisting of power converter-interfaced energy storage, photovoltaic generation, and virtual synchronous generator (VSG), is selected as the research object. Power converters in more-electronics power systems are basically controlled as either AC voltage sources or AC current sources. Therefore, these two types of power converters are designed in detail. Moreover, since power converters are increasingly being expected to provide grid support functions, e.g. the power support, research efforts along this trajectory are reviewed. A prominent power quality issue refers to the current harmonic issue, which can be eased through the use of the proposed advanced passive filters. High-order passive filters allow improved harmonic attenuation with smaller filter sizes. To reap these benefits, the LCL-based trap filters containing extra LC resonant trap(s), represented by LLCL filters, become a hot research topic. In addition, the magnetic integration technique is a parallel research direction for filter size reduction. However, for the integrated LCL filter, the coupling effect between the two inductors acts as a major obstacle. To tackle this issue, the coupling is properly designed and used to form the proposed magnetic integrated LLCL filter. It combines the advantages of magnetic integration and trap filter, resulting in an approximate 50% inductance reduction. Additionally, the series-parallel-resonant LCL (SPRLCL) filter containing one series-resonant trap and one parallel-resonant trap is proposed. It enables excellent filtering and robustness against parameter changes. When a parallel-resonant LC-trap combines with the LCL filter, the LT-C-L filter can be obtained. It is concluded that the LT-C-L filter can be the most promising trap filter due to the advantages of high robustness, roll-off rate, and reduced converter current distortions. For individual power converters, the objective of grid synchronization, particularly under weak grid conditions, may introduce the converter-level instability issue, and this issue can be resolved by reshaping the quadrature-axis (q-axis) converter impedance. The grid synchronization of grid-connected power converters necessitates phase-locked-loops (PLLs). However, the inclusion of PLLs tends to shape the converter impedance as a negative resistance in the q-axis within the control bandwidth of PLLs. Because of this, the interaction between converter impedance and grid impedance may possibly destabilize power conversion systems. To solve this issue, an impedance controller directly relating the q-axis voltage to the q-axis current reference is proposed. The proposed controller manages to reshape the q-axis converter impedance as a positive resistance in the low-frequency band and address the instability concern. The distributed virtual inertia contributed by grid-connected power converters and virtual synchronous generators (VSGs) allow the improvement of the system-level frequency stability. In more-electronics power systems, as synchronous generators being gradually replaced by renewable generators, the lack of inertia issue becomes more obvious. One effective approach for inertia enhancement is to employ the proposed grid-connected power converters with the distributed virtual inertia. By proportionally relating the grid frequency and DC-link voltages, the DC-link capacitors of power converters act as energy buffers and inertia suppliers. Another approach for inertia enhancement lies in the use of VSGs. Although the concept has been well-known, the implementation and coordination control of the energy storage systems (ESSs) in VSGs remain untouched. To fill this research gap, the hybrid ESS (HESS) consisting of a battery and an ultracapacitor is proposed. In this HESS, the ultracapacitor tackles the fast-varying power required by inertia emulation while the battery compensates for the long-term power fluctuations required by the remaining parts of VSGs. Through these methods, the significant improvements of frequency nadir and rate of change of frequency (RoCoF) can be expected, thereby improving the system-level frequency stability. In general, this thesis focuses on and addresses several major power quality and instability issues introduced by power electronics in more-electronics power systems. Specifically, the proposed advanced passive filters are effective solutions to the ever-challenging current harmonic issue. The converter-level instability issue due to PLLs and weak grids is addressed by reshaping the q-axis converter impedance. Moreover, the proposed distributed virtual inertia and VSGs manage to improve the system-level frequency stability. As the renewable integration trend continues, new challenges and opportunities will emerge in more-electronics power systems. With reference to the power quality, the grid support by power converters under adverse grid conditions is considered to be a challenge. For individual power converters with grid support functions, the grid support under weak grids may cause instability concerns, which should be addressed through further research efforts. With respect to the system-level frequency stability, there is a great opportunity to explore the inertia emulation potentials of energy storage units, such as batteries.